A distinct subset of HLA-DR+-regulatory T cells is involved in the induction of preterm labor during pregnancy and in the induction of organ rejection after transplantation - Kisielewicz, Anna; Schaier, Matthias; Schmitt, Edgar; Hug, Friederike; Hänsch, Gertrud Maria; Meuer, Stefan; Zeier, Martin; Sohn, Christof; Steinborn-Kröhl, Andrea (Clinical immunology, 2010)
Regulatory T cells (Tregs) are known to suppress alloimmune responses during pregnancy and post organ transplantation. We demonstrate that a distinct subset of FoxP3+DR+-Tregs among the total CD4+CD127low+/−CD25+-Treg cell pool is critically involved in preterm labor induction and kidney transplant rejection as well. Compared to healthy pregnancies and non-rejecting kidney recipients, we found that the percentage of the FoxP3+DR+-Treg subset was not reduced, but that the level of HLA-DR expression of such Tregs was strongly diminished in preterm laboring women and in patients with acute renal allograft rejection. In addition, both patient collectives showed a significantly reduced suppressive activity of their circulating CD4+CD127low+/−CD25+-Treg cell pool. Our findings propose that the FoxP3+DR+-Treg subset may be decisively responsible for the suppressive activity of the total CD4+CD127low+/−CD25+-Treg cell pool and that the immunologic mechanisms leading to preterm labor necessitating preterm delivery may be similar to those leading to allograft rejection after transplantation.